2010
DOI: 10.4141/cjps09137
|View full text |Cite
|
Sign up to set email alerts
|

Juice quality and polyphenol concentration of fresh fruits and pomace of selected Nova Scotia-grown grape cultivars

Abstract: Juice, fresh fruit and pomace of 10 selected Nova Scotia-grown grape cultivars (five table and five wine cultivars) were evaluated for their physicochemical parameters and major phenolic compounds to determine their suitability in use for developing functional beverages. Colour intensity, total soluble solids, total anthocyanin concentration and antioxidant capacity were significantly higher in juice of wine grape cultivars than in juice of table grape cultivars. Titratable acidity was not significantly differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
5
17
1
Order By: Relevance
“…Burin et al [11] analyzed 3 homemade grape juices for which pH values were 3.30, 3.51 and 3.64; 7 commercial juices which varied from 3.25 to 3.56 and 2 organic juices with measurements of 3.32 and 3.40, their results were compatible with this work. Canadian researchers [23] prepared juices from 10 different cultivars and found pH values of 2.38 to 3.13, displaying a lower number than the lowest observed in this study (2.81 for a white grape juice from the crop of 2013). Gabardo et al (2015) [24] evaluated the protective effect of white grape juice in rats and observed a pH of 3.89 in organic white grape juice and 3.58 in conventionally produced white grape juice, those being notably high values compared to the means of the present work.…”
Section: Resultscontrasting
confidence: 76%
“…Burin et al [11] analyzed 3 homemade grape juices for which pH values were 3.30, 3.51 and 3.64; 7 commercial juices which varied from 3.25 to 3.56 and 2 organic juices with measurements of 3.32 and 3.40, their results were compatible with this work. Canadian researchers [23] prepared juices from 10 different cultivars and found pH values of 2.38 to 3.13, displaying a lower number than the lowest observed in this study (2.81 for a white grape juice from the crop of 2013). Gabardo et al (2015) [24] evaluated the protective effect of white grape juice in rats and observed a pH of 3.89 in organic white grape juice and 3.58 in conventionally produced white grape juice, those being notably high values compared to the means of the present work.…”
Section: Resultscontrasting
confidence: 76%
“…Hue was expressed as a*/b*, while chroma is expressed as (a 2 + b 2 ) 1/2 [10]. Total soluble solids (TSS), pH and titratable acidity (TA) were analyzed in triplicate using previously described methods [11]. Briefly, TSS (Brix) was determined with a hand held refractometer (Model 300016, Super Scientific Ltd., Scottsdale, AZ) at room temperature.…”
Section: Turbidity Colour Brix and Titratablementioning
confidence: 99%
“…When grape skin extracts are added at a concentration of 0.3% (wt/vol), the polyphenol concentration in the resulting cheese is only about 15% lower than in cheeses made with whole grape or grape seed extracts. Ratnasooriya et al (2010) measured the concentration of total polyphenols in a selection of table and wine grape juices. Total polyphenol content in wine grape juices was about 5 times the concentration in table grape juices and averaged 11.3 mg of GAE/L.…”
mentioning
confidence: 99%